Review of instabilities produced by direct contact condensation of steam injected in water pools and tanks. (November 2022) - Muñoz-Cobo, J.L.; Blanco, D.; Berna, C.; Córdova, Y.
Abstract: The purpose of this paper is to review and analyze several types of instabilities as condensation oscillations (CO), stable condensation oscillations (SC), and bubbling condensation oscillation (BCO). These instabilities are produced during the discharge of steam into subcooled pools through vents or spargers. The mechanism of direct contact condensation (DCC) plays an essential role in these instabilities justifying that we review first the fundamental basis of DCC and the jet penetration length for the discharges of pure steam in subcooled water. Then, special attention is devoted to developing correlations for the nondimensional penetration length for ellipsoidal or hemi-ellipsoidal prolate steam jets observed in many experiments, to the heat transfer coefficients of DCC and to the best way to correlate the penetration length. Next, it is analyzed the stability of the steam jets with hemi-ellipsoidal shape in the transition and condensation oscillation regimes and it is computed the subcooling temperature threshold for low and high oscillation frequencies. These results for the subcooling temperature thresholds for low and high frequencies with a hemi-ellipsoidal steam jet are then compared with the results for spherical and cylindrical jets and with the experimental data in an interval of mass fluxes ranging from 0 to 180 k g / m 2 s . In addition, a sensitivity analysis is performed to know the dependence of the low and high frequency liquid temperature thresholds on the vent diameter and the polytropic coefficient. The third part of the paper is devoted to the study of the instabilities produced in the stable condensation (SC) and the interfacial condensation oscillations (IOC) regions of the map. First Hong et al. model (2012) is extended to include the entrainment in the liquid dominated region (LDR), obtaining new expressions for the oscillations frequency that depend on the entrainment coefficient and the expansion of the jet in the liquid dominated region. Finally, the mechanical energy balance is extended to include the momentum transferred to the jet by the condensate steam, obtaining a new equation for the frequency that is compared with Hong et al.'s data for a set of pool temperatures ranging from 35 °C to 90 °C and discharge mass steam fluxes ranging from 200 to 900 k g / m 2 s .